The centers of crisis in the Levant region: The Golan Heights - MARAL BIABANPEIMA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aimed to identify the factors that have contributed to the lengthening of the Golan crisis and to lay out potential outcomes for the conflict over the territory of Golan.Methodology: The researchers used a qualitative approach, gathering their information through a careful examination of the existing literature.Findings: We found that the credibility of a region’s economy, military, and sense of identity are all important in determining whether or not a regional dispute can be resolved, supporting the hypothesis that political elites’ resolve and expertise are crucial. Thus, the Golan dispute settlement has become more complicated due to a lack of determination and the necessary skills among political elites and Golan’s insufficient economic, military, and identity credibility.